(untitled) (Baghdad Science Journal, 2015)
Diabetes mellitus (DM) has been defined as a clinical syndrome that is characterized by abnormal carbohydrate metabolism. The chronic hyperglycemia of diabetes is associated with long term damage, dysfunction, and failure of different organs, especially the liver .This study was conducted to assess the effect obesity and insulin resistance on liver enzymes in diabetic Iraqi patients.A comparative study of (90) Iraqi adults divided to three subgroup(30) obese ,(30) nonobese diabetic patients and(30)person had used as control. The analysis included Liver enzyme ALP,ALT,AST,GGT ,Fasting Plasma Glucose (FBG) , Lipid Profile , Hemoglobin A1C , insulin and homeostasis model assessment of insulin resistance (HOMA IR) were measured. Subjects were excluded from this study if they had liver disease, alcohol intake, medications for lowering lipid, insulin treatment, pregnant women and women taking contraceptive pills . The study shows significantly higher of liver enzymes level ( gamma glutamyl transpeptidase (GGT), alkaline phosphatase, Aspartate Amino Transferase , Alanine Transaminase) in obese diabetic patients compared with non-obese diabetic patients and control subject and HOMA IR showed significantly higher in obese diabetic patients compared with non-obese with diabetic patients and control (P < 0.05). The lipids level showed significantly higher in obese diabetic patients compared with non-obese diabetic patients and control.The HbA1c level showed higher significantly in obese diabetic patients compared with control and ther is a posative correlation between insulin and HOMA IR , ALP in obeses diabetic patients while there was negative correlation between ALT and cholesterol in obese group and with HbA1c in control group. The liver enzymes level of(alkaline phosphatase, alanine transaminase, aspartate transaminase gama glutaminase transferase ) is significantly higher in obese diabetic patients than non –obese diabetic patients and control group , also There was posative correlation between ALP and HOMA IR while there was negative correlation between ALT and cholesterol in obese group and with HbA1c in control group .